Investigation of procoagulant activity in extracellular vesicles isolated by differential ultracentrifugation. Issue 1 (1st January 2018) - Nielsen, Thøger; Kristensen, Anne Flou; Pedersen, Shona; Christiansen, Gunna; Kristensen, Søren Risom
ABSTRACT: Tissue factor (TF) is the main initiator of coagulation and procoagulant phospholipids (PPL) are key components in promoting coagulation activity in blood. Both TF and PPL may be presented on the surface of extracellular vesicles (EVs), thus contributing to their procoagulant activity. These EVs may constitute a substantial part of pathological hypercoagulability that is responsible for triggering a higher risk of thrombosis in certain patients. The aim of this study was to describe a model system for the isolation of EVs required for investigating their effect on coagulation. Differential ultracentrifugation (DUC) with and without a single washing step was used to isolate and evaluate the procoagulant capacity of EVs from healthy volunteers through analysis of thrombin generation and PPL activity. Ultracentrifugation at 20, 000 × g and 100, 000 × g resulted in pellets containing larger vesicles and smaller vesicles, respectively. Isolation yield of particle concentration was assessed by nanoparticle tracking analysis. Immunoelectron microscopy and western blotting revealed vesicles positive for the commonly used EV-marker CD9. Plasma proteins and lipoproteins were co-isolated with the EVs; however, application of a washing step clearly diminished the amount of contaminants. The isolated EVs were capable of enhancing thrombin generation, mainly due to PPL predominantly present in pellets from 20, 000 × g centrifugation, and correlated with the activity measured by a PPL activity assay. Thus, DUC was proficient for the isolation of EVs with minimal contamination from plasma proteins and lipoproteins, and the setup can be used to study EV-associated procoagulant activity. This may be useful in determining the procoagulant activity of EVs in patients at potentially increased risk of developing thrombosis, e.g. cancer patients. Abbreviations : TF: Tissue factor; PL: Phospholipids; EVs: Extracellular vesicles; FXa: Activated coagulation factor X; TGA: Thrombin generation assay; PPL: Procoagulant phospholipids; DUC: Differential ultracentrifugation; NTA: Nanoparticle tracking analysis; TEM: Transmission electron microscopy; SPP: Standard pool plasma; CTI: Corn trypsin inhibitor; 20K: 20, 000 × g ; 100K: 100, 000 × g ; FVIII: Coagulation factor VIII